THE MODERATING EFFECTS OF ETHNIC IDENTIFICATION ON THE RELATIONSHIP BETWEEN PARENTAL MONITORING AND SUBSTANCE USE IN MEXICAN HERITAGE ADOLESCENTS IN THE SOUTHWEST UNITED STATES - Nagoshi, Julie L. (2011)
The purpose of this study was to assess the combined effects of ethnic identification and perceived parental monitoring on the substance use of a sample of 162 male and 192 female Mexican heritage seventh grade adolescents. Parental monitoring predicted lower risk for substance use. An interaction of ethnic identification by parental monitoring was observed with parental monitoring exhibiting stronger effects in decreasing use of alcohol use among boys who scored low on ethnic identification. For girls, decreased substance use was predicted by stronger parental monitoring coupled with high ethnic identification. Results are discussed in terms of how the youth’s ethnic identification is a distinct process from acculturation, and how ethnic identification may operate as an added protective factor in conjunction with parental monitoring, as protective factors against adolescent substance abuse.